2005
DOI: 10.1249/01.mss.0000174888.22930.e0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Immunological Responses Relative to High-Altitude Exposure in Mountaineers

Abstract: Changes in the composition of intestinal microbiota may be associated with indicators of an immunological challenge and may result in an increased health risk of mountaineers during exposure to very high altitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 23 publications
(24 reference statements)
2
47
0
Order By: Relevance
“…Changes in body composition result from hypoxia-related suppression of muscle protein synthesis results in WL [17, 20]. Hypoxia-induced intestinal dysfunction contributes to WL especially above 5500 m, and the reason was suggested to be changes in the intestinal flora due to hypoxia [17, 23]. …”
Section: Skeletal Muscle and Body Weightmentioning
confidence: 99%
“…Changes in body composition result from hypoxia-related suppression of muscle protein synthesis results in WL [17, 20]. Hypoxia-induced intestinal dysfunction contributes to WL especially above 5500 m, and the reason was suggested to be changes in the intestinal flora due to hypoxia [17, 23]. …”
Section: Skeletal Muscle and Body Weightmentioning
confidence: 99%
“…Most data reported in the literature on the effects of hypoxia on the human immune system were generated from field studies conducted in high-altitude mountain environments (Chouker et al, 2005;Kleessen et al, 2005;Krupina et al, 1974Krupina et al, , 1977Mirrakhimov et al, 1989;Thake et al, 2004;Tiollier et al, 2005). Chronic high-altitude exposure alters the immunological status.…”
Section: Discussionmentioning
confidence: 99%
“…These changes persisted for as long as five months (Mirrakhimov et al, 1989). In addition, high-altitude exposure is often associated with inflammation and increased risk of infection (Kleessen et al, 2005). A recent study showed also the cumulative negative effect of physical exercise and hypoxia on salivary immunoglobulin A levels during an 18-day "living high-training low" protocol (Tiollier et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When fecal bacterial population groups and serum responses in seven mountaineers on a 47-day expedition to the Himalaya were examined, there was distinct alteration in the microfl ora above 5,000 m [ 75 ]. Bifi dobacteria and species belonging to the Atopobium , Coriobacterium , and Eggerthella lenta group decreased, whereas potentially pathogenic bacteria of the γ-subdivision of Proteobacteria and specifi c Enterobacteriaceae such as Escherichia coli increased.…”
Section: Short-term Visitorsmentioning
confidence: 99%